La formación económica de la sociedad argentina, volumen II De la acumulación originaria al desarrollo de su especificidad hasta 1930 - Iñigo Carrera, Juan (Biblioteca Historia de América, 2022)
In order for the process of knowledge to confront its object in the integrity of its concrete determination, it is necessary to start from the simplest form of the object in question, and to reproduce it with thought by virtually accompanying it in the unfolding of its determinations, however that these appear to be the opposite of that simpler content of theirs. Such is the course that this research follows in order to answer about the specific national form with which Argentine society acts as a subject in the process of development of the productive forces of work. This research does not consist of the historical unfolding of the course followed by Argentine society throughout the period considered, as a process whose unity is given simply by dealing with the same national scope. On the contrary, its course has as its axis the evidence of the features that this historical development presents as expressions of the existence of a specific determination of the form that the Argentine national process of capital accumulation takes.